Determinasi Nasabah Dalam Memilih Produk Asuransi Sebagai Jaminan Masa Depan Pasca New Normal - Al Ihsan, Muhammad Ali (Jurnal Manajemen Akuntansi (JUMSI), 2021)
This study aims to determine the determination of the customer in choosing the insurance after the new normal. This study was conducted on the customers of PT. Life Insurance Bumiputra 1912 Rantauprapat. The number of samples taken as many as 100 respondents by using the technique of sampling purposivie sampling.Before testing the hypothesis test is conducted data quality of the first test, classic assumption test, namely; normality test, multicollinearity, and hiteroskedastisitas. After testing the hypothesis that partial test (t test) and simultaneous test (F test). The results showed that income has positive and significant effect on purchasing decisions, education is not positive and significant effect on purchasing decisions, knowledge has positive and significant effect on purchasing decisions and simultaneous income, education and knowledge influence the buying decision using insurance products.